(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study examines the relationship between economic factors and nutritional preferences in shaping food consumption patterns within emerging economies. Rising income levels, urbanization, food prices, and consumer awareness have significantly influenced dietary choices and purchasing behavior. The study investigates how household income, affordability, and perceived nutritional value affect consumers’ selection of food products. Using empirical evidence from emerging markets, the findings indicate that economic conditions play a critical role in determining access to nutritious foods, while nutritional awareness positively influences healthier consumption decisions. The results further suggest that price sensitivity remains a major barrier to adopting balanced diets among lower-income groups. The study contributes to the literature on consumer economics and public health by highlighting the need for policies that promote affordable nutrition and sustainable food systems. The findings offer valuable insights for policymakers, businesses, and health practitioners seeking to improve consumer well-being.